Investigating the Use of Conjunction in A Movie: A Case on Discourse Analysis - Purba, Ridwin; Siahaan, Entika Cintami; Nainggolan, Sindy Gloria; Sihombing, Bonita Anjelina; Sirait, Setia Oktaviana; Herman, Herman (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the conjunctions in the M3GAN movie. The researchers wanted to investigate and analyze the application of conjunctions and the dominant types of conjunctions in M3GAN movies. Researchers used qualitative descriptive methods. Researchers collected data by watching M3GAN movies, paying attention to the subordinating conjunctions, then writing down the data in notes. Based on the research results, researchers found 115 data that used subordinate conjunctions in the M3GAN movie. The percentage of use of subordinate conjunctions from the M3GAN movie can be seen based on the types of subordinate conjunctions, namely there are 0.8% comparison conjunction data, 19% cause conjunction data, 74.7% apposition conjunction data, 5.1% time conjunction data, and 0% contrast conjunction data. The total states that the apposition conjunction is the highest score for the use of subordinate conjunctions in the M3GAN movie and the lowest score is the contrast conjunction.